(untitled) (Docentes 2.0 Journal, 2025)
University teaching plays an evident role in the academic training of future professionals and the development of society—the present study aimed to know the perceptions and experiences of university teachers hired in a public university. The research was based on the interpretive paradigm under the phenomenological method, with a qualitative approach, phenomenological design, descriptive-interpretive, and cross-sectional. The sample was selected for convenience and ATLAS.ti V.24 interviewed three contracted teachers from a public university, which was used for data analysis. The results found that the perception of contracted teachers regarding the management of university authorities is mostly negative. The emotion that contracted teachers experience most is satisfaction for a duty fulfilled. Professional experience, sympathy, and respect for the student were some of the strengths the teachers claimed to have. Finally, regarding the proposals for improvement, contracted university teachers propose job stability, appointment of contracted teachers, better communication between university authorities and teachers, no discrimination between contracted and appointed university teachers, and finally, incentives and recognition of teaching efforts. It is concluded that the results found can be generalized to other similar environments. Likewise, the negative perception of contracted university teachers with university management is a reality that can affect teacher production and, therefore, needs to be addressed as a priority.